(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2023)
Crimes under federal jurisdiction are often committed by criminal associations or criminal organizations, also using legal entities, and usually leave no financial traces. These specificities require state agents to have greater expertise in order to uncover criminal conduct, imposing the use of investigative techniques that differ from those commonly employed, which is why telephone and telematic monitoring appears to reinforce criminal prosecution activity.